A Knowledge-based Theory of the Multinational Economic Organization. Issue 6 (December 2016) - Low, Kathleen Yi Jia; Ho, Elsen Yen-Chen
Abstract : The study of the MNC has been deeply influenced by transaction-cost economics over the last four decades (Buckley and Casson, 1976; Dunning, 2000; Hennart, 1982; Rugman, 1981). Coase's (1937) analysis of the boundaries of the firm became the foundation of one of the most important and enduring areas of international business research: the study of internalization and the theory of the multinational corporation. However, recent research has argued that a capability-based approach to the MNC provides a more complete analysis than traditional internalization theory (Cantwell, 2014; Teece, 2014). In this paper, we argue that efforts to subsume the analysis of internalization within the study of capabilities exhibit a fundamental flaw. They neglect a critical distinction Williamson (1999) made between economic organization and the firm. Drawing on concepts from the knowledge-based view of the firm, we develop a more comprehensive approach to multinational economic organization that deals with questions of both scope and form of organization.